Doing arts-based master's thesis supervision/writing in teacher education: A new materialist approach to supervision - Sofia Jusslin; Gunilla Eklund (Cappelen Damm Akademisk NOASP, 2022)
Arts-based research has been proposed to be a new paradigm in teacher education, but research on supervising arts-based educational research in master's theses in education remains scarce. Recently, researchers have begun re-thinking supervision with relational, more-than-human ontologies, acknowledging that it encompasses doings and relational becomings produced by a multiplicity of human and non-human bodies. However, little attention has been given to the becoming for both student and supervisor, and this research has been limited to doctoral supervision. Originating through a student-supervisor relationship, the study explored the entangled supervision/thesis writing processes to produce an understanding of arts-based educational master's thesis supervision in teacher education. The analytical questions were: (1) What doings make a difference when supervising and writing an arts-based educational master's thesis, and (2) what are their opportunities and challenges for teacher education? A diffractive analysis produced doings of thinking-together with/in theory and arts-based educational research practice, be(com)ing-teacher and be(com)ing-supervisor, and be(com)ing-with-the-thesis. The doings focused on the master's thesis project but extended its boundaries. The doings drew on the past concerning previous experiences and knowledges, were fueled by present mutual interests, and affected future teaching practices. The study holds implications by providing valuable insights into arts-based educational research supervision in teacher education.